2019
DOI: 10.3390/ijms20205042
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Transcriptomics and Metabolomics for Pepper (Capsicum annuum L.) in Response to Heat Stress

Abstract: Heat stress (HS), caused by extremely high temperatures, is one of the most severe forms of abiotic stress in pepper. In the present study, we studied the transcriptome and metabolome of a heat-tolerant cultivar (17CL30) and a heat-sensitive cultivar (05S180) under HS. Briefly, we identified 5754 and 5756 differentially expressed genes (DEGs) in 17CL30 and 05S180, respectively. Moreover, we also identified 94 and 108 differentially accumulated metabolites (DAMs) in 17CL30 and 05S180, respectively. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 78 publications
0
46
0
Order By: Relevance
“…Luckily, the recent advances in technologies allowing large-scale “–omics” analyses accelerate this process. The studies in this Special Issue add valuable pieces of the puzzle related to stress responses by: (i) reporting novel potent regulators and the mechanisms through which they exert their effects [ 15 , 17 , 18 , 19 ]; (ii) throwing light on previously unexplored components [ 16 ] or the pathways involved in particular stress types [ 11 , 12 , 13 ]; or (iii) exploring strategies to mitigate the detrimental effects [ 14 ]. We are confident that they will inspire further productive research in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luckily, the recent advances in technologies allowing large-scale “–omics” analyses accelerate this process. The studies in this Special Issue add valuable pieces of the puzzle related to stress responses by: (i) reporting novel potent regulators and the mechanisms through which they exert their effects [ 15 , 17 , 18 , 19 ]; (ii) throwing light on previously unexplored components [ 16 ] or the pathways involved in particular stress types [ 11 , 12 , 13 ]; or (iii) exploring strategies to mitigate the detrimental effects [ 14 ]. We are confident that they will inspire further productive research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although the heat shock-responsive genes were induced in both cultivars, the upregulation was more pronounced in the tolerant 17CL30. The authors suggested that the higher levels of glutathione and glutathione S-transferases play a critical role in pepper response to heat shock and might contribute to the heat tolerance [ 11 ].…”
Section: Genetic and Systems Biology Approaches Revealing The Compmentioning
confidence: 99%
“…Proline and arginine accumulations were also observed in drought-tolerant sesame genotype, besides an increase of abscisic acid, lysine, aromatic and branched chain amino acids, 4-aminobutanoic acid, saccharopine, 2-aminoadipate, and allantoin). Metabolomics—also in combination with other-omics—can explain the drought-tolerance mechanism in drought-tolerant wild and/or ancestral genotypes, providing useful information for breeding purposes, as wild soybean ( Glycine soja ) (Wang et al, 2019a ) and Brachypodium distachyon (Lenk et al, 2019 ), among others, as well as the salt-tolerant mechanisms of the halophyte for food or pharmaceutical purposes (Chen et al, 2019 ).…”
Section: Disruptive Quantitative Precision Methods For Stress Assementioning
confidence: 99%
“…Two pepper cultivars 17CL30 (HT) and 05S180 (HS) were obtained from Vegetable Institution of Hunan Academy of Agricultural Science. The seed germination and seedling management of pepper were carried out as previously described [49]. Six-leaf stage seedlings of HT and HS cultivars were subjected to heat stress at 40℃, and the leaves were harvested at 0, 3, 28 and 48 h for physiological assays and proteomic analysis.…”
Section: Plant Materials and Heat Treatmentmentioning
confidence: 99%